The Effect of Tocilizumab on the outcome of patients with severe COVID-19 with cytokine storm syndrome in a sample of Iraqi patients - Abdul Hameed Alqaseer; Alaa Kareem Dhayef; Ammar Waham Ashor (Journal of the Pakistan Medical Association, 2024)
Objective: To determine whether tocilizumab improved outcomes of patients hospitalised with severe coronavirus disease-2019 cytokine storm syndrome. Method: The case-control study was conducted at Al-Yarmouk Teaching Hospital, Baghdad, and Al Shatra General Hospital, Thi Qar, Iraq, from September 2020 to March 2021, and comprised patients with severe acquired respiratory syndrome-corona virus-2 pneumonia who were not candidates for mechanical ventilation and received a single-dose intravenous infusion of tocilizumab 8mg/kg in group A. The outcomes were compared with patients in group B who received only standard care. Data was analysed using SPSS 26. Results: Of the 60 patients, 30(50%) were in group A; 22(73.3%) males and 8(26.7%) females with mean age 56.63±10.92 years. There were 30(50%) patients in control group B; 24(80%) males and 6(20%) females with mean age 54.8±6.18 (p>0.05). Group A showed significant changes compared to group B in the levels of interleukin-6, serum ferritin, D-dimer, procalcitonin, lymphocytes count and oxygen saturation (p<0.05). Mortality rate was not significantly different between the groups (p>0.05). Conclusions: Majority of the acute phase inflammatory markers were reduced significantly by treatment with tocilizumab. Key Words: Tocilizumab, fibrin, Interleukin, Procalcitonin, Cytokine, Infusions, Intravenous, Oxygen Saturation, Respiration, Artificial, Coronavirus, Lymphocytes, Ferritins